Dividend Policy and Stock Price Volatility: A Study on Indonesian Manufacturing Companies - Ridloah, Siti; Putri, Rizkia Duwi; Noekent, Vitradesie; Waliuddin, Achmad Nauval (Management Analysis Journal, 2022)
The purpose of this study was to examine and analyze the effect of dividend policy on stock price volatility in manufacturing companies listed on Indonesia Stock Exchange from 2019-2020. This study also examines other factors that ar thought to have an effect on dividend policy and stock price volatility, such as: firm size, earning voolatility, and leverage. This research method uses a quantitative approach, using secondary data derived from the company’s annual financial report. Purposive sampling method uses in this study. The sample used was 62 companies with a total of 124 observations. This study use multiple regression method. SPSS 16 is an analytical tool used in this study. The empirical findings of this study indicate that dividend policy has a negative effect on stock price volatility. If the dividends paid increases, the possibility of stock price volatility will decrease. The control variable of firm size dan leverage have no effect on stock price volatility. Furthermore, it is also found that there is a positive influence between the control variable of earning volatility and stock price volatility.